2013
DOI: 10.1073/pnas.1303967110
|View full text |Cite
|
Sign up to set email alerts
|

Target specificity among canonical nuclear poly(A) polymerases in plants modulates organ growth and pathogen response

Abstract: Polyadenylation of pre-mRNAs is critical for efficient nuclear export, stability, and translation of the mature mRNAs, and thus for gene expression. The bulk of pre-mRNAs are processed by canonical nuclear poly(A) polymerase (PAPS). Both vertebrate and higher-plant genomes encode more than one isoform of this enzyme, and these are coexpressed in different tissues. However, in neither case is it known whether the isoforms fulfill different functions or polyadenylate distinct subsets of pre-mRNAs. Here we show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(92 citation statements)
references
References 49 publications
4
88
0
Order By: Relevance
“…We also found that da3-1 had small root meristems with a reduced cell number (Supplemental Figure 4), suggesting that DA3 influences cell proliferation in an organ-dependent manner. Similar contextdependent effects were also seen for da1-ko1 dar1-1 dar2-1 and paps1-1 mutants (Vi et al, 2013;Peng et al, 2015).…”
Section: Da3 Is Required For Endoreduplicationsupporting
confidence: 64%
See 1 more Smart Citation
“…We also found that da3-1 had small root meristems with a reduced cell number (Supplemental Figure 4), suggesting that DA3 influences cell proliferation in an organ-dependent manner. Similar contextdependent effects were also seen for da1-ko1 dar1-1 dar2-1 and paps1-1 mutants (Vi et al, 2013;Peng et al, 2015).…”
Section: Da3 Is Required For Endoreduplicationsupporting
confidence: 64%
“…Several factors have been known to affect organ growth in an organ-dependent manner. For example, loss-of-function mutations in poly(A) polymerase PAPS1 caused large flowers and small leaves (Vi et al, 2013). The simultaneous disruption of DA1, DA1-related protein 1 (DAR1), and DAR2 resulted in large seeds and flowers, small leaves, and short roots (Peng et al, 2015).…”
Section: Da3 Is Required For Endoreduplicationmentioning
confidence: 99%
“…Here, we showed that oxt6 and mips1 oxt6 mutants were more susceptible than wild-type control plants to the virulent bacterium Pst. Furthermore, it recently has been shown that the reduced activity of PAPS1, a poly(A) polymerase that is recruited to add the poly(A) tail after the cleavage of the nascent premRNA, leads to a constitutive pathogen response via an EDS1/PAD4-dependent mechanism Vi et al, 2013). Likewise, the Arabidopsis protein FPA, which functions independently of the CPSF complex to regulate alternative polyadenylation, has been shown to negatively modulate the flagellin response (Lyons et al, 2013).…”
Section: A Role For Mrna Maturating Complexes In the Regulation Of Dementioning
confidence: 99%
“…Furthermore, the E3 ubiquitin-ligase BIG BROTHER (BB) can repress plant organ growth, probably by marking cellular proteins for degradation (Disch et al, 2006). Recently, poly(A) polymerases (PAPS) have been shown to influence leaf size and shape, probably by affecting the expression of specific subsets of relevant genes (Vi et al, 2013). In Cardamine hirsuta, the ribosome-associated protein SIMPLE LEAF3 also affects leaf growth and leaflet development (Kougioumoutzi et al, 2013).…”
Section: The Mechanics Of Leaf Initiationmentioning
confidence: 99%